2010
DOI: 10.1007/s00062-010-0038-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolution from an Infundibulum of the Posterior Communicating Artery to a Saccular Aneurysm

Abstract: Infundibular widening of cerebral arteries can develop into true aneurysms. Mid-term and long-term follow-up MRI (e.g., in yearly intervals) is advised for infundibula with a diameter of 3 mm or more. In patients with other aneurysm(s), with a documented de novo aneurysm formation or with a familial occurrence of aneurysms, the risk of evolution of an infundibulum to a saccular aneurysm may be increased and follow-up should be even more stringent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 12 publications
0
26
1
Order By: Relevance
“…The nature of these dilations is a matter of discussion 1. Some authors consider an ID as a preaneurysmal lesion,2–4 while others believe that is a normal variant 3.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of these dilations is a matter of discussion 1. Some authors consider an ID as a preaneurysmal lesion,2–4 while others believe that is a normal variant 3.…”
Section: Introductionmentioning
confidence: 99%
“…3 8 12–24 Thirteen of these patients were female (81.3%). The median age at the time of initial diagnosis was 38 years (range 23–55 years).…”
Section: Resultsmentioning
confidence: 99%
“…Fischer et al 3 reported a middle-aged woman who presented with SAH. While the source of hemorrhage was found to be a vertebral artery aneurysm, during the initial diagnosis a PCoA ID was also identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations